Nonwoven fabric, and sound-absorbing material including nonwoven fabric
A nonwoven fabric with specific fiber diameters and production methods enhances sound absorption in the medium and low frequency range, addressing productivity issues of existing materials.
Patent Information
- Application Number
- JP2024174564
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-03
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2040-10-16
AI Technical Summary
Existing sound absorbing materials lack effective sound absorption properties in the medium and low frequency range and have low industrial productivity due to the use of fibers with low productivity manufacturing methods like electrospinning.
A nonwoven fabric composed of cellulose fine fibers with a fiber diameter of 100 nm to 2000 nm and short fibers with a diameter of 0.1 μm to 10 μm, produced through wet-laid processes, achieving a specific average pore size and sound absorption in the medium and low frequency range.
The nonwoven fabric exhibits excellent sound absorption in the medium and low frequency range, with a sound absorption coefficient of 0.5 or more below 3000 Hz and 0.2 from 2000 to 6000 Hz, while maintaining high productivity.
Smart Images

Figure 2024177416000003 
Figure 2024177416000001 
Figure 2024177416000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a nonwoven fabric and a sound-absorbing material using the nonwoven fabric. [Background technology]
[0002] When a vehicle is running, various noises are generated, such as noise from the engine and drivetrain, road noise, and wind noise. Conventionally, sound-absorbing materials have been used to suppress these noises and create a comfortable interior space. Meanwhile, the electrification of automobiles has progressed in recent years, and the quietness of drivetrains in particular has improved. Due to these technological changes, sounds that were not previously recognized as noise, specifically sounds in the mid-low frequency range below 3000 Hz, are beginning to be recognized as noise. In the above-mentioned range, it is known that nonwoven fabrics containing fibers with a small fiber diameter and composite structures in which a surface layer is provided on a porous body exhibit excellent sound absorption properties. For example, the following Patent Document 1 shows a laminated structure composed only of fibers with a fiber diameter of less than 450 nm, and shows that it has excellent sound absorption properties in the low frequency range of 1000 Hz or less. However, the fibers contained in the structure are produced by an electrospinning method, which is very poor in productivity and difficult to put into practical use industrially. Furthermore, Patent Document 2 listed below shows a structure in which cellulose nanofibers are applied to one side of a nonwoven fabric, and describes that by using this as a skin material for a sound-absorbing material, it is possible to control the air resistance and obtain suitable sound-absorbing performance. However, there is no description about sound-absorbing properties in the low and mid-frequency range. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2018 / 143430 [Patent Document 2] International Publication No. 2017 / 006993 Summary of the Invention [Problem to be solved by the invention]
[0004] In view of the above-mentioned conventional techniques, an object of the present invention is to provide a skin material for a composite sound-absorbing material that has excellent sound-absorbing properties in the low and mid-frequency ranges and can be produced easily. [Means for solving the problem]
[0005] The inventors conducted intensive research and repeated experiments to solve the above problems, and as a result, they discovered that by uniformly mixing short fibers having a fiber diameter of 0.1 μm or more and 10 μm or less and cellulose fine fibers having a fiber diameter of 100 nm or more and 2000 nm or less to form a nonwoven fabric having an average pore size in a specific range, a composite sound-absorbing material using this nonwoven fabric as a skin material has excellent sound-absorbing properties in the mid-to-low frequency range of 3000 Hz or less while also having sound-absorbing properties in a wide frequency range, thereby completing the present invention.
[0006] That is, the present invention is as follows. [1] A nonwoven fabric comprising cellulose fine fibers having an average fiber diameter of 100 nm or more and 2000 nm or less and staple fibers having an average fiber diameter of 0.1 μm or more and 10 μm or less, characterized in that the average flow diameter measured with a perm porometer is 1 μm or more and 30 μm or less. [2] The nonwoven fabric according to [1], containing the cellulose fine fibers in an amount of 1% by mass or more and less than 20% by mass. [3] The nonwoven fabric according to [1] or [2], wherein the cellulose fine fibers are type II cellulose. [4] The nonwoven fabric according to any one of [1] to [3] above, which is a wetlaid nonwoven fabric. [5] A sound-absorbing material made of the nonwoven fabric according to any one of [1] to [4]. [6] A composite sound-absorbing material comprising the nonwoven fabric according to any one of [1] to [4] above and a porous material other than the nonwoven fabric laminated thereto. [7] The composite sound-absorbing material according to [6], which has a maximum sound absorption value at or below 3000 Hz in a normal incidence measurement method conforming to JIS A 1405, said maximum value being 0.5 or more, and has a sound absorption coefficient of 0.2 or more over the entire range from 2000 to 6000 Hz. Effect of the Invention
[0007] The nonwoven fabric according to the present invention has excellent sound absorbing properties in the low and mid-frequency ranges, has high productivity, and can be suitably used as a skin material for composite sound absorbing materials. Therefore, it can be suitably used as a skin material for composite sound absorbing materials used in automobiles, housing, and home appliances in particular. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a diagram showing the results of sound absorption coefficient measurement in Example 1, Example 2, and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to these embodiments. One embodiment of the present invention is a nonwoven fabric comprising cellulose fine fibers having an average fiber diameter of 100 nm or more and 2000 nm or less and staple fibers having an average fiber diameter of 0.1 μm or more and 10 μm or less, and characterized in that the mean flow diameter measured with a perm porometer is 1 μm or more and 30 μm or less.
[0010] (Nonwoven fabric) The nonwoven fabric of this embodiment is preferably a nonwoven fabric having a structure in which cellulose fine fibers having an average fiber diameter of 100 nm or more and 2000 nm or less and staple fibers having an average fiber diameter of 0.1 μm or more and 10.0 μm or less are uniformly integrated. The nonwoven fabric of this embodiment has a dense structure with fine fiber gaps and has a very small amount of breathability, so that when sound penetrates the gaps between the fibers, the vibrational energy of the sound is converted into thermal energy through friction with the ultra-fine fibers, and the fibers themselves also vibrate in response to the vibrational energy of the sound, thereby further converting it into thermal energy.
[0011] (Cellulose Microfibers) The nonwoven fabric of this embodiment contains cellulose fine fibers. Here, the cellulose fine fibers are cellulose fibers that have been finely divided using at least one type of physical means, and are synonymous with general names such as cellulose nanofibers, CNF, CeNF, and MFC (microfibrillated cellulose).
[0012] (Cellulose microfiber diameter) The average fiber diameter of the cellulose fine fibers in the nonwoven fabric in this embodiment is 100 to 2000 nm from the viewpoint of the effect of finely refining the internal structure of the nonwoven fabric by the cellulose fine fibers. By highly refining, the internal structure of the nonwoven fabric also becomes finer, but the productivity of the cellulose fine fibers deteriorates, and the pore size of the nonwoven fabric becomes too small, which significantly restricts the air permeability and makes it difficult to obtain a sound absorbing effect. On the other hand, if the degree of refining is low, the internal structure of the nonwoven fabric also becomes rough, so the average fiber diameter of the cellulose fine fibers is preferably 200 to 1000 nm, more preferably 300 to 800 nm. By adjusting to this range, not only the finely refining structure restricts the air permeability of the nonwoven fabric, but the cellulose fine fibers themselves vibrate and can contribute to sound absorption, and high sound absorption properties are obtained in all frequency bands.
[0013] In the present disclosure, the average fiber diameter of the cellulose fine fibers means the fiber diameter of the cellulose fine fibers used as a raw material for nonwoven fabric, and is measured according to the following procedure. (1) Cellulose fine fibers are dispersed in tert-BuOH to a solids concentration of 50 ppm. If the cellulose fine fibers are in powder form, the solids concentration is taken into consideration and adjusted to the above concentration. If the cellulose fine fibers are dispersed in a medium such as water or an organic solvent, the dispersion medium is removed as much as possible by filtration or centrifugation, and the cellulose fine fibers are dispersed in tert-BuOH in the same manner as in the case of a powder. The dispersion process in tert-BuOH is carried out using a high-shear homogenizer (for example, IKA, product name "Ultra Turrax T18") under the following processing conditions: a rotation speed of 25,000 rpm for 5 minutes. (2) 5 μL of the dispersion is dropped onto an Os-coated Si wafer and quickly spread over the entire surface. (3) (2) is dried on a hot plate heated to 130°C or in an oven. (4) Observe the sample (3) above using a high-resolution scanning electron microscope (SEM) at a magnification of 500 to 2000 times, and photograph at least 10 fields of view. (5) In each image obtained in (4), measure the fiber diameter of at least 10 randomly selected fibrous substances. In this case, if branched fibers are present, the diameters of the trunk and branch portions are measured separately. (6) The average value of all the measured fiber diameters is the average fiber diameter of the cellulose fine fibers.
[0014] (Cellulose raw material) The raw material for cellulose fine fibers includes so-called wood pulp such as coniferous pulp and hardwood pulp as a raw material for type I cellulose, and non-wood pulp. Examples of non-wood pulp include cotton-derived pulp such as cotton linter pulp, hemp-derived pulp, bagasse-derived pulp, kenaf-derived pulp, bamboo-derived pulp, and straw-derived pulp. Cotton-derived pulp, hemp-derived pulp, bagasse-derived pulp, kenaf-derived pulp, bamboo-derived pulp, and straw-derived pulp respectively refer to purified pulp obtained from raw materials such as cotton lint or cotton linter, hemp-based abaca (for example, many of which are produced in Ecuador or the Philippines), zaisal, bagasse, kenaf, bamboo, and straw through delignification by cooking treatment, and a refining process and a bleaching process for the purpose of removing hemicellulose. In addition, purified products such as seaweed-derived cellulose and sea squirt cellulose can also be used as raw materials for cellulose fine fibers. Furthermore, as the raw material for type II cellulose, cut yarns of regenerated cellulose fibers and cut yarns of cellulose derivative fibers can also be used as the raw material for cellulose fine fibers, and cut yarns of ultrafine yarns of regenerated cellulose or cellulose derivatives obtained by electrospinning can also be used as the raw material for cellulose fine fibers or the cellulose fine fibers themselves. These raw materials can be used alone or in combination. The average fiber diameter can be adjusted by mixing multiple raw materials.
[0015] (Micronization of cellulose) The above-mentioned raw material can be refined to obtain cellulose fine fibers. In one embodiment, a pretreatment step is performed before the refinement treatment. In the pretreatment step, it is effective to make the raw pulp in a state that is easy to refine by autoclaving under water immersion at a temperature of 100 to 150°C, enzyme treatment, or a combination of these. These pretreatments not only reduce the load of the refinement treatment, but also expel impurity components such as lignin and hemicellulose present on the surfaces and gaps of the microfibrils constituting the cellulose fibers into the aqueous phase, thereby increasing the α-cellulose purity of the finely refined fibers, and therefore may be effective in improving the heat resistance of the cellulose fine fibers.
[0016] In the refining process, the raw pulp is dispersed in water and refined using a known refining device such as a beater, a disc refiner (double disc refiner), a high-pressure homogenizer, etc. The suitable treatment concentration during refining varies depending on the device used, and may be set arbitrarily. The average fiber diameter of the cellulose fine fibers can be controlled by the above-mentioned cellulose raw material, the pretreatment conditions before the fine fiber treatment (e.g., autoclave treatment, enzyme treatment, beating treatment, etc.), the fine fiber treatment conditions (selection of the type of equipment, operating pressure, number of passes, etc.), or a combination of these. Here, the average fiber diameter may be controlled by combining a plurality of conditions regarding the cellulose raw material, pretreatment, fine fiber treatment, etc.
[0017] (Cellulose microfiber content) The nonwoven fabric of this embodiment preferably contains cellulose fine fibers in an amount of 1% by mass or more and less than 20% by mass. Here, the content of cellulose fine fibers refers to the solid weight ratio of cellulose fine fibers to the solid weight of short fibers contained in the nonwoven fabric. By setting the content of cellulose fine fibers in this range, the structure of the nonwoven fabric is not too dense and has the breathability required for sound absorption. If the content of cellulose fine fibers is low, the sound absorption effect of the cellulose fine fibers cannot be obtained, but if the content is high, the rigidity of the entire nonwoven fabric increases, making it difficult to vibrate and making it difficult to obtain the sound absorption effect, so the content of cellulose fine fibers is more preferably 3% by mass or more and 15% by mass or less, and most preferably 5% by mass or more and 10% by mass or less.
[0018] (Crystalline form of cellulose) The crystalline form of the cellulose fine fibers of this embodiment is preferably type II cellulose. Type II cellulose fibers tend to be less easily micronized than type I cellulose, and the average fiber diameter is easily controlled within a suitable range. Type II cellulose is also preferred because the fibers are less likely to aggregate during drying in the production of nonwoven fabrics, and sound absorbing effects in the low frequency range are easily obtained.
[0019] (Short Fiber) The nonwoven fabric of this embodiment includes short fibers in addition to cellulose fine fibers. Here, short fibers in this disclosure refer to fibrous materials made of substances other than cellulose and fibers having a fiber length of 10 mm or less. As the short fibers, any of natural fibers, synthetic fibers, and semi-synthetic fibers can be used. Examples of polymers constituting the short fibers include thermoplastic resins such as polyolefins, polyesters, polyamides (aromatic or aliphatic), acrylic polymers, polyvinyl alcohol, polylactic acid, polyphenylene ether, polyoxymethylene, and polyphenylene sulfide, epoxy resins, thermosetting modified polyphenylene ether resins, thermosetting polyimide resins, urea resins, allyl resins, silicon resins, benzoxazine resins, phenolic resins, unsaturated polyester resins, bismaleimide triazine resins, alkyd resins, furan resins, melamine resins, polyurethane resins, and aniline resins. These short fibers may be used alone or in combination.
[0020] (Average diameter of short fibers) The short fibers contained in the nonwoven fabric in this embodiment have an average fiber diameter of 0.1 μm or more and 10.0 μm or less. By using short fibers having an average fiber diameter in this range, when they are mixed with the cellulose fine fibers, they are uniformly mixed, and a nonwoven fabric with a sufficiently fine internal structure is obtained. In addition, by using short fibers having a fiber diameter of 10.0 μm or less, the short fibers are easily vibrated, and a sound absorbing effect is easily obtained. If the average fiber diameter of the short fibers is large, the cellulose fine fibers and the short fibers are easily localized inside the nonwoven fabric, but if it is too small, the internal structure of the nonwoven fabric becomes too dense, and the breathability required for sound absorption cannot be obtained. Therefore, it is preferably 1.0 μm or more and 8.0 μm or less, and most preferably 1.0 μm or more and 6.0 μm or less.
[0021] The average fiber diameter of the short fibers is measured by the following procedure. (1) Disperse the short fibers in water at a solids concentration of 0.05% by mass using a household blender mixer or the like. (2) The dispersion liquid is dropped onto a slide glass to prepare a preparation. (3) Observe (2) above using a digital microscope at a magnification of 500 to 2000 times, and photograph at least five fields of view. (4) In each image obtained in (3), measure the fiber diameter of at least 10 randomly selected fibrous substances. In this case, if branched fibers are present, the fiber diameter at the stem portion shall be measured. (5) The average value of all the measured fiber diameters is the average fiber diameter of the short fibers.
[0022] (Average flow diameter of nonwoven fabric) The nonwoven fabric of this embodiment is characterized in that the average flow diameter measured by a palm porometer is in the range of 1.0 μm to 30.0 μm. By being in this range, the nonwoven fabric has a very small amount of breathability, and a good sound absorbing effect can be obtained in the medium and low frequency range. If the average flow diameter is too small, the breathability is lost and the sound absorbing effect cannot be obtained, but if it is too large, the breathability cannot be restricted when used as a skin material. Therefore, the average flow diameter is preferably 3 μm to 20 μm, more preferably 4 μm to 15 μm, and most preferably 5 μm to 13 μm. The average flow diameter of the nonwoven fabric is measured using a palm porometer (model: CFP-1200AEX) manufactured by PMI. PMI's Galwick (surface tension = 15.6 dynes / cm) is used as the immersion liquid, and the measurement is performed by the half-dry method in accordance with ASTM E1294-8.
[0023] (Wet-processed nonwoven fabric) The nonwoven fabric in this embodiment is preferably a wet nonwoven fabric. Here, the wet nonwoven fabric means a nonwoven fabric manufactured using a papermaking method or a hydroentanglement method in at least a part of the nonwoven fabric manufacturing process. Cellulose fine fibers are generally finely divided in water, and when dried, the finely divided fibers reaggregate and are not easily redispersed. Therefore, it is desirable that the cellulose fine fibers are brought into the nonwoven fabric forming process in a never-dry state after finely dividing, and are preferably formed into a nonwoven fabric by a wet method.
[0024] (Nonwoven fabric count) In the nonwoven fabric of this embodiment, the basis weight is 10 g / m 2 More than 1000g / m 2 The following range is preferable. Within this range, the nonwoven fabric can be efficiently produced, has a good texture, and has suitable breathability as a sound absorbing material. 2 If the thickness is more than 1000g / m, the thickness of the nonwoven fabric increases and suitable sound absorption characteristics are obtained in the low and mid-frequency range. 2 If the weight is less than this, appropriate air permeability is obtained and sound absorbing effect is easily obtained. Therefore, the weight is more preferably 30 g / m 2 More than 500g / m 2 Less than 50 g / m 2 More than 300g / m 2 The following is the result.
[0025] (Thickness of nonwoven fabric) The nonwoven fabric of this embodiment preferably has a thickness in the range of 0.1 mm to 3.0 mm, which allows space saving when used as a sound absorbing material. The thickness of the nonwoven fabric is measured according to the following procedure. (1) Cut the nonwoven fabric into a 20cm x 20cm piece. (2) Using an ABS digital indicator ID-CX (manufactured by Mitutoyo Corporation), measure the thickness at five different points on the nonwoven fabric. At this time, a flat gauge head with a diameter of 15 mm is used. (3) The average value of the five points obtained in (2) above is regarded as the thickness of the nonwoven fabric.
[0026] (Bulk density of nonwoven fabric) The bulk density of the nonwoven fabric of this embodiment is 0.05 g / cm 3 More than 0.50g / cm 3 It is preferable that the bulk density is 0.1 g / cm or less. When the bulk density is in this range, appropriate breathability is obtained and sound absorbing effect is easily obtained. It is more preferable that the bulk density is 0.1 g / cm or less. 3 More than 0.4g / cm 3 and more preferably 0.15 g / cm 3 More than 0.35g / cm 3 It is. The bulk density is calculated by the following formula. Bulk density [g / cm 3 ]=Weight [g / m 2 ] / Thickness [μm]
[0027] (Air resistance of nonwoven fabric) The air resistance of the nonwoven fabric of this embodiment is preferably 10.0s / 100mL or less. When the air resistance is in this range, it means that the cellulose fine fibers are uniformly present inside the nonwoven fabric, the internal structure is finely refined and porous, and the fabric has minute air permeability. The smaller the air resistance is, the better the air permeability is, and the easier it is to obtain a sound absorbing effect. Therefore, the air resistance is preferably 5.0s / 100mL or less, more preferably 3.0s / 100mL or less, and most preferably 2.0s / 100mL or less. The air resistance of the present disclosure means the result of measuring the permeation time of 100mL of air using a Gurley densometer (for example, manufactured by Toyo Seiki Co., Ltd., model G-B2C), and is measured by the following procedure.
[0028] (1) Cut the nonwoven fabric into a 20cm x 20cm piece. (2) Using a Gurley densometer (e.g., Toyo Seiki Co., Ltd., Model G-B2C), measure the air resistance of five different nonwoven fabrics. However, for samples with an air resistance exceeding 1000 s / mL, measure using an Oken air resistance tester (e.g., Asahi Seiko Co., Ltd., Model EG01) instead of the Gurley densometer. (3) The average value of the five points obtained in (2) above is regarded as the air resistance of the nonwoven fabric.
[0029] (Applications of nonwoven fabric) The nonwoven fabric of this embodiment can be suitably used as a sound absorbing material. It may be used alone or multiple sheets may be stacked. When used alone, it has low sound absorption in the low frequency range, and the sound absorption rate increases as the frequency increases. When multiple sheets are stacked, it shows a peak sound absorption rate due to surface vibration, and the peak shifts to the low frequency side depending on the number of sheets stacked.
[0030] (Laminated sound absorbing material) The nonwoven fabric of this embodiment is preferably used as a skin material by laminating it to a porous material other than the nonwoven fabric to be used as a composite sound absorbing material. Here, examples of the porous material include nonwoven fabric, knitted fabric, fiber sheets such as felt, mats, breathable polyurethane foam, breathable rubber foam, etc. By forming such a laminated structure, good sound absorbing properties are exhibited.
[0031] (Lamination method with porous materials) The nonwoven fabric of the present embodiment can be laminated to a porous material by various means, such as a method of directly heating the nonwoven fabric and bonding it by heat fusion, or a method of applying a hot melt adhesive to the surface of the nonwoven fabric by curtain spray or the like, and then heating the nonwoven fabric side to heat fusion.
[0032] (Sound absorption coefficient of composite sound absorbing material) The laminated sound-absorbing material using the nonwoven fabric of this embodiment exhibits particularly high sound absorption, i.e., a maximum sound absorption value, in the mid-low frequency range of 3000 Hz or less in the normal incidence measurement method conforming to JIS-1405, and the maximum value is preferably 0.5 or more, and the sound absorption coefficient is preferably 0.3 or more in the entire range of 2000 Hz to 6000 Hz. By having such sound-absorbing characteristics, it is possible to absorb sound in the mid-low frequency range of 3000 Hz or less, which is generally difficult to absorb, while having a sound-absorbing effect over a wide range of frequencies.
[0033] When this nonwoven fabric is used as a surface material for a composite sound absorbing material, its performance is evaluated as follows. (1) A circular disk with a diameter of 28.8 mm is cut out from nonwoven fabric and naturally laminated with coarse wool felt with a thickness of 10 mm to create a composite sound-absorbing material. (2) The sound absorption coefficient of the composite sound absorbing material is measured using a normal incidence sound absorption coefficient measurement system DS-2000 (manufactured by Ono Sokki Co., Ltd.) in accordance with JIS A 1405. At this time, the nonwoven fabric in this embodiment is measured on the incident side of the sound wave. EXAMPLES
[0034] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these.
[0035] (Cellulose microfiber diameter) The average fiber diameter of the cellulose fine fibers was measured according to the following procedure. (1) After removing as much water as possible from the aqueous dispersion of cellulose fine fibers by filtration, the mixture was dispersed in tert-BuOH to a solids concentration of 50 ppm. A high-shear homogenizer (IKA, product name "Ultra Turrax T18") was used for the dispersion treatment, and the treatment conditions were: rotation speed 25,000 rpm x 5 minutes. (2) 5 μL of the dispersion was dropped onto an Os-coated Si wafer and quickly spread over the entire surface. (3) The above (2) was dried on a hot plate heated to 130°C. (4) The above (3) was observed under a high-resolution scanning electron microscope (SEM) at a magnification of 2000 times, and 10 fields of view were photographed. (5) In each image obtained in (4) above, the fiber diameters of 10 randomly selected fibrous substances were measured. At this time, when branched fibers were present, the diameters of the trunk and branched portions were measured separately. (6) The average value of all the measured fiber diameters was taken as the average fiber diameter of the cellulose fine fibers.
[0036] (Average diameter of short fibers) The average fiber diameter of the short fibers was measured by the following procedure. (1) Short fibers were dispersed in water at a concentration of 0.05% by mass using a household blender mixer or the like. (2) The dispersion was dropped onto a slide glass to prepare a preparation. (3) Observe (2) above using a digital microscope at a magnification of 500 times and photograph at least five fields of view. (4) In each image obtained in (3) above, 10 fibrous substances were randomly selected and washed, and the fiber diameters were measured. (5) The average value of all the measured fiber diameters was taken as the average fiber diameter of the short fibers.
[0037] (Average flow diameter of nonwoven fabric) The average flow diameter of the nonwoven fabric was measured using a palm porometer (model: CFP-1200AEX) manufactured by PMI Co., Ltd. The immersion liquid was Galwick manufactured by PMI Co., Ltd. (surface tension = 15.6 dynes / cm), and the measurement was performed by the half-dry method in accordance with ASTM E1294-8.
[0038] (Nonwoven fabric count) The basis weight of the nonwoven fabric was calculated in accordance with JIS P 8124.
[0039] (Thickness of nonwoven fabric) The thickness of the nonwoven fabric was measured by the following procedure. (1) The nonwoven fabric was cut into a size of 20 cm x 20 cm. (2) The thickness of the nonwoven fabric was measured at five different points using an ABS digital indicator ID-CX (manufactured by Mitutoyo Corporation). A flat gauge head with a diameter of 15 mm was used. (3) The average value of the five points obtained in (2) above was regarded as the thickness of the nonwoven fabric.
[0040] (Air resistance of nonwoven fabric) The air resistance of the nonwoven fabric was measured by the following procedure. (1) The nonwoven fabric was cut into a size of 20 cm x 20 cm. (2) Using a Gurley densometer (Toyo Seiki Co., Ltd., model G-B2C), the air resistance was measured for five different nonwoven fabrics. (3) The average value of the five points obtained in (2) above was regarded as the air resistance of the nonwoven fabric.
[0041] (Sound absorption coefficient of composite sound absorbing material) A circular disk with a diameter of 28.8 mm was cut out from the nonwoven fabric in each Example and Comparative Example, and naturally laminated with a coarse wool felt with a thickness of 10 mm to form a composite sound absorbing material. The sound absorption coefficient of the composite sound absorbing material was measured using a normal incidence sound absorption coefficient measuring system DS-2000 (manufactured by Ono Sokki Co., Ltd.) in accordance with JIS A 1405. The measurement was performed so that the nonwoven fabric was on the incident side of the sound wave. The substrate used in the measurement was prepared and used according to the description of each Example and Comparative Example described below.
[0042] (CNF-A, CNF-B) Tencel cut yarn (3 mm long), a regenerated cellulose fiber obtained from Sojitz Corporation, was placed in a cleaning net, a surfactant was added, and the fiber surface was washed repeatedly in a washing machine to remove the oil. After that, the fiber was dispersed in water to a solid content of 1.5% by mass, and beaten using an SDR14 lab refiner (pressurized disk type) manufactured by Aikawa Iron Works Co., Ltd. The beating treatment was carried out while measuring the fiber diameter as necessary, and the cellulose fine fiber slurry at the point when the average fiber diameter reached 950 nm was designated as CNF-A (solid content concentration: 1.5% by mass). CNF-A was further refined using the above-mentioned disc refiner, and the beating water slurry was then refined using a high-pressure homogenizer (NS015H, manufactured by Niro Soavi, Italy) to obtain a cellulose fine fiber slurry with an average fiber diameter of 390 nm, which was designated CNF-B (solid content concentration: 1.5% by mass).
[0043] (CNF-C, CNF-D, CNF-E) Linter pulp, which is natural cellulose obtained from Japan Pulp and Paper Co., Ltd., was used and soaked in water so that the linter pulp was 4% by mass. Then, heat treatment was performed in an autoclave at 130°C for 4 hours, and the resulting swollen pulp was washed with water multiple times to obtain purified linter pulp impregnated with water. The purified linter pulp was then dispersed in water so that the solid content was 1.5% by mass, to obtain 400 L of dispersion. This was beaten using an SDR14 lab refiner (pressure type DISK type) manufactured by Aikawa Iron Works Co., Ltd. as a disc refiner device. The beating treatment was carried out while measuring the fiber diameter as necessary, and the cellulose fine fiber slurry at the point when the average fiber diameter reached 2,500 nm was designated as CNF-C (solid content concentration: 1.5% by mass). The CNF-C was further beaten using the above-mentioned disc refiner, and the cellulose fine fiber slurry at the point where the average fiber diameter became 118 nm was designated as CNF-D (solid content concentration: 1.5% by mass). Next, CNF-D was subjected to a micronization process using a high-pressure homogenizer (NS015H manufactured by Niro Soavi, Italy), and the cellulose microfiber slurry at the point where the average fiber diameter reached 98 nm was named CNF-E (solid content concentration 1.5% by mass).
[0044] (Short Fiber A) Short fibers (3.0 mm long) made of polyethylene terephthalate were weighed, water was added, and the mixture was stirred for 4 minutes in a household mixer to obtain a short fiber slurry (solid content concentration: 0.05% by mass). The average fiber diameter of the short fibers in the slurry was 3.0 μm.
[0045] (Short Fiber B) Short polypropylene fibers (2.0 mm long) were weighed, water was added, and the mixture was stirred for 4 minutes in a household mixer to obtain a short fiber slurry (solid content concentration: 0.05% by mass). The average fiber diameter of the short fibers in the slurry was 5.3 μm.
[0046] (Short Fiber C) Short polypropylene fibers (3.0 mm long) were weighed, water was added, and the mixture was stirred for 4 minutes in a household mixer to obtain a short fiber slurry (solid content concentration: 0.05% by mass). The average fiber diameter of the short fibers in the slurry was 9.2 μm.
[0047] (Short Fiber D) Short polypropylene fibers (5.0 mm long) were weighed, water was added, and the mixture was stirred for 4 minutes in a household mixer to obtain a short fiber slurry (solid content concentration: 0.05% by mass). The average fiber diameter of the short fibers in the slurry was 10.6 μm.
[0048] Example 1 A nonwoven fabric was produced using CNF-B and short fiber A according to the following procedure. CNF-B and short fiber A were added to pure water at a solids weight ratio of 5:95 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) with a basis weight of 300 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain nonwoven fabric S1. The physical properties of the obtained nonwoven fabric are shown in Table 1 below.
[0049] Example 2 A nonwoven fabric was produced using CNF-B and short fiber A according to the following procedure. CNF-B and short fiber A were added to pure water at a solids weight ratio of 5:95 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) so that the basis weight was 100 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain a nonwoven fabric S2. The physical properties of the obtained nonwoven fabric are shown in Table 1 below.
[0050] Example 3 A nonwoven fabric was produced using CNF-B and short fiber B according to the following procedure. CNF-B and short fiber B were added to pure water at a solids weight ratio of 15:85 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) so that the basis weight was 100 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain a nonwoven fabric S3. The physical properties of the obtained nonwoven fabric are shown in Table 1 below.
[0051] Example 4 A nonwoven fabric was produced using CNF-B and short fiber B according to the following procedure. CNF-B and short fiber B were added to pure water at a solids weight ratio of 15:85 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) so that the basis weight was 50 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain a nonwoven fabric S4. The physical properties of the obtained nonwoven fabric are shown in Table 1 below.
[0052] Example 5 A nonwoven fabric was produced using CNF-B and short fiber C according to the following procedure. CNF-B and short fiber C were added to pure water at a solids weight ratio of 15:85 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) so that the basis weight was 100 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain nonwoven fabric S5. The physical properties of the obtained nonwoven fabric are shown in Table 1 below.
[0053] Example 6 A nonwoven fabric was produced using CNF-D and short fiber A according to the following procedure. CNF-D and short fiber A were added to pure water at a solids weight ratio of 5:95 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) so that the basis weight was 100 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain nonwoven fabric S6. The physical properties of the obtained nonwoven fabric are shown in Table 1 below.
[0054] Example 7 A nonwoven fabric was produced using CNF-A and short fiber B according to the following procedure. CNF-A and short fiber B were added to pure water at a solids weight ratio of 30:70 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) so that the basis weight was 200 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain nonwoven fabric S7. The physical properties of the obtained nonwoven fabric are shown in Table 1 below.
[0055] Comparative Example 1 A nonwoven fabric was produced using CNF-D and short fiber A according to the following procedure. CNF-D and short fiber A were added to pure water at a solids weight ratio of 20:80 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) so that the basis weight was 100 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain nonwoven fabric R1. The physical properties of the obtained nonwoven fabric are shown in Table 2 below.
[0056] Comparative Example 2 A nonwoven fabric was produced using CNF-E and short fiber B according to the following procedure. CNF-E and short fiber B were added to pure water at a solids weight ratio of 15:85 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) so that the basis weight was 100 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain nonwoven fabric R2. The physical properties of the obtained nonwoven fabric are shown in Table 2 below.
[0057] Comparative Example 3 A nonwoven fabric was produced using CNF-B and short fiber D according to the following procedure. CNF-B and short fiber D were added to pure water at a solids weight ratio of 30:70 to give a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) so that the basis weight was 100 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2 The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain nonwoven fabric R3. The physical properties of the obtained nonwoven fabric are shown in Table 2 below.
[0058] Comparative Example 4 A nonwoven fabric was produced using CNF-C and short fiber A according to the following procedure. CNF-C and short fiber A were added to pure water at a solids weight ratio of 50:50 to a final solids concentration of 0.5%. The slurry was stirred for 4 minutes in a household mixer to prepare a papermaking slurry. The above prepared papermaking slurry was applied to a batch-type papermaking machine (Kumagaya Riki Kogyo Co., Ltd., automatic square sheet machine, 25 cm x 25 cm, 80 mesh) equipped with a filter cloth (Shikishima Canvas Co., Ltd., TT35) with a basis weight of 300 g / m 2 Then, the pressure was reduced to 50 KPa relative to atmospheric pressure and papermaking (dehydration) was carried out. The wet paper made of the concentrated composition in a wet state placed on the filter cloth was peeled off from the wire and subjected to a pressure of 1 kg / cm 2The nonwoven fabric was dried for about 120 seconds in a drum dryer with a surface temperature set to 130° C. to obtain nonwoven fabric R4. The physical properties of the obtained nonwoven fabric are shown in Table 2 below.
[0059] [Table 1]
[0060] [Table 2] [Industrial Applicability]
[0061] The nonwoven fabric according to the present invention has excellent sound absorbing properties in the low and mid-frequency ranges, has high productivity, and can be suitably used as a skin material for composite sound absorbing materials. Therefore, it can be suitably used as a skin material for composite sound absorbing materials used in automobiles, housing, and home appliances in particular.
Claims
1. A nonwoven fabric comprising cellulose fine fibers having an average fiber diameter of 100 nm or more and 2000 nm or less and staple fibers having an average fiber diameter of 0.1 μm or more and 10 μm or less, the nonwoven fabric being characterized in that the average flow diameter measured by a perm porometer is 1 μm or more and 30 μm or less.
2. The nonwoven fabric according to claim 1 , comprising the cellulose fine fibers in an amount of 1% by mass or more and less than 20% by mass.
3. The nonwoven fabric according to claim 1 or 2, wherein the cellulose fine fibers are type II cellulose.
4. The nonwoven fabric according to any one of claims 1 to 3, which is a wetlaid nonwoven fabric.
5. A sound absorbing material made of the nonwoven fabric according to any one of claims 1 to 4.
6. A composite sound-absorbing material comprising the nonwoven fabric according to any one of claims 1 to 4 laminated with a porous material other than the nonwoven fabric.
7. 7. The composite sound-absorbing material according to claim 6, which has a sound absorption maximum value at 3000 Hz or less, the maximum value being 0.5 or more, and has a sound absorption coefficient of 0.2 or more over the entire range from 2000 to 6000 Hz, in a normal incidence measurement method conforming to JIS A 1405.
Citation Information
Patent Citations
Sound absorbing heat insulating material
JP2006285086A
Polyphenylene sulfide paper, polyphenylene sulfide oxide paper, and method for producing them
JP2009084713A
Low density fiber paper containing hydrophobic nanofiber
JP2020066830A
Skin material sheet, method for producing same and sound-absorbing material
WO2017006993A1
Laminate sound-absorbing material including ultrafine fiber
WO2018143430A1
